Structure-Activity Relationship Studies of Indolglyoxyl-Polyamine Conjugates as Antimicrobials and Antibiotic Potentiators - Melissa M. Cadelis; Tim Liu; Kenneth Sue; Florent Rouvier; Marie-Lise Bo; Jean Michel Brunel; Brent R. Copp (MDPI AG, 2023)
Antibiotic resistance is a growing global health threat, requiring urgent attention. One approach to overcome antibiotic resistance is to discover and develop new antibiotic enhancers, molecules that work with legacy antibiotics to enhance their efficacy against resistant bacteria. Our previous screening of a library of purified marine natural products and their synthetic analogues led to the discovery of an indolglyoxyl-spermine derivative that exhibited intrinsic antimicrobial properties and was also able to potentiate the action of doxycycline towards the difficult to treat, Gram-negative bacterium Pseudomonas aeruginosa. A set of analogues have now been prepared, exploring the influence of indole substitution at the 5- and 7- positions and length of the polyamine chain on biological activity. While limiting cytotoxicity and/or hemolytic activities were observed for many analogues, two 7-methyl substituted analogues (23b and 23c) were found to exhibit strong activity towards Gram-positive bacteria with no detectable cytotoxicity or hemolytic properties. Different molecular attributes were required for antibiotic enhancing properties, with one example identified, a 5-methoxy-substitiuted analogue (19a), as being a non-toxic, non-hemolytic enhancer of the action of two tetracycline antibiotics, doxycycline and minocycline, towards P. aeruginosa. These results provide further stimulation for the search for novel antimicrobials and antibiotic enhancers amongst marine natural products and related synthetic analogues.